Association Between Atrial Uptake on Cardiac Scintigraphy With Technetium-99m-Pyrophosphate Labeled Bone-Seeking Tracers and Atrial Fibrillation. (17th May 2022) - Hussain, Muzna; Krywanczyk, Alison; Donnellan, Eoin; Martyn, Trejeeve; Hassan, Ossama Abou; Alkharabsheh, Saqer; Watson, Chris; Tang, W.H.; Kwon, Deborah; Cremer, Paul; Cheng, Feixiong; Kanj, Mohamed; et al.
Abstract : Background: Transthyretin cardiac amyloidosis (ATTR-CA) is an increasingly recognized disease, in which atrial fibrillation (AF) has been shown to be prevalent. Cardiac scintigraphy with technetium-99m-pyrophosphate (99mTc-PyP) labeled bone-seeking tracers is used to noninvasively make the diagnosis of ATTR-CA, based on ventricular myocardial uptake. Assessment of atrial wall uptake (AU) on 99mTc-PyP is currently not used in the clinical setting Methods: We analyzed a cohort of patients referred for 99mTc-PyP scan at a tertiary center to explore AU and associations between any and incident AF, ATTR-CA, and all-cause mortality. Results: Among 580 patients included, 296 patients (51%) had a diagnosis of AF; 164 patients (28%) had scans consistent with ATTR-CA while 117 patients (20%) had AU. Of 117 patients with AU, 107 (91%) had any AF. In contrast, of 463 patients without AU 191(41%) had any AF. Of those with AU, 59/117(50%) patients had a 99mTc-PyP diagnosis of ATTR-CA while 58/117(50%) patients did not have such a diagnosis ( P =1.00). Patients with AU had significantly more any AF (hazard ratio [HR], 1.03 [95% CI, 1.02–1.04]; P <0.001), independent of ATTR-CA diagnosis and sex. On multivariable Cox proportional hazards analyses adjusting for age, AU, ATTR-CA diagnosis, sex, smoking, hypertension, diabetes, left ventricular ejection fraction, and coronary artery disease, both age (HR, 1.03 [95% CI, 1.02–1.04]; P <0.0001) and AU (HR, 2.68 [95% CI, 2.11–3.41]; P <0.0001) were independently associated with the development of any AF. Freedom from incident AF at 1-year was significantly lower in patients with AU, both in patients with and without ATTR-CA respectively (HR, 2.27 [95% CI, 1.37–3.78]; P <0.0001 versus HR, 2.21 [95% CI, 1.46–3.34]; P <0.0001). Conclusions: In a consecutive cohort of patients undergoing 99mTc-PyP scans, 20% had AU, which was statistically associated with any AF, independently of ATTR-CA diagnosis and sex. AU was associated with significantly lower freedom from incident AF at 1-year. Overlooking AU on 99mTc-PyP scans could potentially miss an earlier disease manifestation, or an additional risk factor for any/incident AF.